Management of the 4 A’s of Tourism: Addressing Shortcomings and Enhancing Services in Gebong Memarong Traditional Village - Marwani, Iga Safa; Pusparini, Marissa; Lestari, Zakia Ayu; Sabri, Fadillah; Usman, Ali (International Journal of Magistravitae Management, 2023)
Air Abik hamlet, situated in Gunung Muda village, Belinyu Sub-District, Bangka Regency, Bangka Belitung Islands Province, Indonesia, is renowned for its rich cultural heritage embodied by the Lom tribe, holding immense potential for tourism development as a vibrant tourist village. However, the management of Gebong Memarong, a traditional accommodation facility in the area, faces challenges hindering its optimal operation. This research adopts a descriptive qualitative approach, utilizing observation, interviews, and documentation analysis to understand the management practices surrounding Gebong Memarong comprehensively. The findings reveal deficiencies in amenities and ancillary services, indicating a critical need for stakeholders’ attention to bolstering support facilities within the tourism village. Furthermore, this research advocates for enhanced managerial competencies to address operational gaps and ensure the sustainable management of homestay facilities. It offers valuable insights into improving accommodation management within culturally significant tourism destinations, with implications for sustainable tourism development strategies in similar contexts.